Demographic Variations and Their Impacts on Biochemical and Hematological Profiles in Patients with Chronic Renal Failure - Meri, Marwa Ahmed; Abar, Ensaf Saleh; Al-Bdery, Alaa Shahid Jassim (Medical Science Journal for Advance Research, 2026)
Background: Chronic renal failure permanently harms the kidney and results in significant metabolic derangements. It is one of the key global health challenges of our times. Aim: The study evaluated the biochemical and hematological changes in the patients affected by chronic renal failure as compared to healthy ones. Methods: A total of 80 subjects participated in the study, out of which 40 were diagnosed as CRF patients. 40 age-matched healthy subjects were done as well. Serum urea, creatinine, uric acid, albumin, calcium, and hemoglobin level measurement will be done using standard laboratory methods. Patients and controls exhibited clear differences. Results: In the group of individuals with chronic renal failure the serum urea reached a mean value of 179.41 ± 58.27 mg/dL and that of creatinine 8.80 ± 1.79 mg/dL which were statistically significantly elevated (p < 0.001). 25% of cases were seen in individuals aged 51–60 years, which was the highest proportion. The calcium level observed was lower at 8.06 ± 1.37 mg/dL and the albumin level was reduced to 3.85 ± 0.75 g/dL. There was also evidence of renal anemia as noted by the decline of hemoglobin to a mean value of 9.45 ± 1.96 g/dL (P < 0.001). Conclosion: The chronic renal failure disorder causes an impairment of the filtration and endocrine kidney functions. The first stages of biochemical marker monitoring and management of metabolic risk factors, may slow down the disease. According to the laboratory changes observed, the clinician can assess the severity of the disease and anticipate developing complications like cardiovascular disorders and renal bone disease.